NiS2 Nanocubes Coated Ti3C2 Nanosheets with Enhanced Light‐to‐Heat Conversion for Fast and Efficient Solar Seawater Steam Generation. Issue 7 (17th April 2021) - Wang, Zhenguo; Xu, Wangqiong; Yu, Ke; Gong, Shijing; Mao, Huibing; Huang, Rong; Zhu, Ziqiang
Abstract : Recently, 2D materials have emerged in the field of light‐to‐heat conversion. However, it is urgent to find a simple and effective method to reduce the light reflectivity of the 2D surface to improve the light‐to‐heat conversion efficiency. A 2D nano‐self‐assembly material coating (NiS2 @Ti3 C2 ) realized by a simple hydrothermal method, which enables unique‐sized nano‐NiS2 crystals and 2D Ti3 C2 –MXenes to self‐assemble on a 3D scale, is innovatively proposed. Such a preparation method can construct a unique multilayer structure for multistage diffuse reflection of incident light, so that the MXene nanomaterial can achieve a light absorption rate of >90% in a wide spectral range. The composite is theoretically verified through optical simulation and first principles, and a higher light‐to‐heat conversion performance is achieved experimentally (61.7 °C surface equilibrium temperature, 1 sun). Compared with other similar materials, the assembled MXene seawater steam generator achieves a higher steam generation rate (1.27 kg m −2  h −1 ) and light‐to‐heat conversion efficiency (83.84%) under 1 sun. This material structure can maximize MXene active materials' utilization and provide ideas for modifying other 2D photothermal materials. Abstract : The Ti3 C2 MXene self‐assembled photothermal conversion material coated with NiS2 nanocrystals is synthesized by a step‐by‐step hydrothermal method. Theoretical calculations, finite element simulations, and experimental methods have confirmed that it has a high absorption rate for a wide solar spectrum and achieves a high photothermal conversion efficiency and rapid seawater evaporation rate.